Shisha Smoking: Knowledge and Perception among Male Medical University Students in Dammam City, Saudi Arabia - Amr Ahmed Sabra; Attia Z. Taha (Journal of High Institute of Public Health, 2011)
Background: There is growing evidence that tobacco use other than cigarettes is spreading across all world regions. Few reports have been published about shisha smoking among university students. It is important that medical students, the future medical practitioners, have adequate knowledge of smoking-related diseases and skills in smoking cessation. Aim of the study: Was to assess the level of knowledge about shisha smoking and to identify behaviors and perceptions concerning shisha smoking among male medical students at University of Dammam, Eastern Province, Saudi Arabia. Methods: This was a cross-sectional study conducted at University of Dammam, among male medical students of the three Colleges namely, Medicine, Applied Medical Sciences, and Dentistry. A total of 371 students were included in the study. Data were collected through an interviewer-administered questionnaire pertaining to the following: socio-demographic characteristics, prevalence of shisha smoking, knowledge about hazardous effects of shisha and students’ perceptions concerning reasons of initiation, continuation and future plans of shisha smoking. Descriptive statistics and Chi-square test were used for statistical analysis. Results: The majority of students were Saudis (98.8%) and single (97.8%). The overall knowledge score about the adverse health consequences of shisha smoking showed that 21.6% had poor knowledge and 78.4% had good knowledge. The students of college of Medicine (85.3%) had better knowledge than Applied Medical Sciences (71.6%) and Dentistry (60.8%) college students, (P<0.001). Poor knowledge about shisha smoking was found among 28.0% of first level students in comparison with 18.2% and 15.7% second and third level students consecutively, (P=<0.05). About 57.4% of shisha smokers were thinking of quitting smoking, while the remaining 42.6% were not thinking or had no future plans to quit smoking. Conclusion: There is unsatisfactory level of knowledge abouth shisha smoking hazards among male university students in medical colleages with poor intention to quit smoking. Thus medical schools should design, teach and implement training of medical students about smoking and its related diseases to provide future medical practitioners with the knowledge and skills they need to effectively intervene with smokers as well as to have positive perceptions about their future role as medical practitioners.